Investigating the Efficacy of RSI Divergence in Nifty & Non-Nifty Stocks - Vishnoi, Shravan (Digital Repository of Theses - SSBM Geneva, 2024)
This dissertation examines the efficacy Relative Strength Index (RSI) divergences by comparing two distinct types of stock categories: “a highly liquid large-cap stock (RELIANCE)” and “a smaller, more volatile non-NIFTY 50 stock (LIBERTSHOE).” The key findings indicate that divergence formation durations differ between NIFTY 50 and non-NIFTY 50 stocks, with RELIANCE exhibiting longer formation periods, especially for bearish divergences, while LIBERTSHOE demonstrates quicker resolution due to higher volatility. Both stocks show similar overall success rates for divergences, though bullish signals are more reliable. Furthermore, the study confirms that RSI divergence-based trading strategies are profitable in both stock categories, with RELIANCE providing higher returns due to greater liquidity. This research underscores the importance of tailoring technical analysis strategies to specific stock characteristics and highlights the potential of RSI divergences as a tool for optimizing trading strategies in diverse market environments.